Biased penalty calls in the National Hockey League. (18th August 2016) - Beaudoin, David; Schulte, Oliver; Swartz, Tim B.
Abstract : This paper investigates penalty calls in the National Hockey League (NHL). Our study shows that there are various situational effects that are associated with the next penalty call. These situational effects are related to the accumulated penalty calls, the goal differential, the stage of the match and the relative strengths of the two teams. We also investigate individual referee effects across the NHL. © 2016 Wiley Periodicals, Inc. Statistical Analysis and Data Mining: The ASA Data Science Journal, 2016